Penetapan Kadar Hesperidin Pada Seduhan Kulit Jeruk Keprok (Citrus Nobilis L.) - Dhirisma, Fitria; Pinasti, Rahayu (Jurnal Pharmacopoeia, 2025)
Tangerine peel (Citrus nobilis L.) has a high content of flavonones, namely hesperidin, naringin and narirutin which can be used as antidiabetics by increasing insulin release through increasing serum insulin and C-peptide levels. The drying method can affect the total phenolic content of orange peel so that the air-dried drying method is reported to be able to produce high phenol levels. The purpose of this study was to determine the hesperidin levels in tangerine peel infusion (Citrus nobilis L.). This type of research is an experimental laboratory study in the form of a test to determine the hesperidin levels in tangerine peel infusion using Uv-Vis speccrophotometry. The sample was 2 grams of orange peel infusion, the hesperidin standard was made in a series of levels of 2, 4, 6, 8, 10 ppm. The wavelength is obtained from the absorbance of the hesperidin reference solution, then a standard curve is made and a linear equation is obtained. The maximum wavelength of hesperidin is 282.7 nm according to the literature. The standard curve of hesperidin is obtained y = 0.0448x + 0.0265 with a correlation coefficient (r) of 0.9994. Determination of hesperidin levels in tangerine peel infusion was carried out in 3 replications and obtained R1 8.559 ppm, R2 7.517 and R3 6.649 with an average of 7.588 ppm. The hesperidin levels in 2 grams of tangerine peel infusion using UV-Vis spectrophotometry were 151.77 ppm.